ANALISIS KINERJA PELAYANAN PUBLIK PERUSAHAAN DAERAH AIR MINUM (PDAM) TIRTA KENCANA KOTA SAMARINDA - Rinda Sandayani Karhab; Muhammad Jamal Amin; Rosa Anggraeny (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
This study aims are to determines: Public Satisfaction Index value of public service performance, provided service performance and interest grade towards customers, performance and importance grade compatibility of service elements according to the customers, and to discover public service dimensions that are urgently required to be improved which became public satisfaction measurement in order to increase the level of the public satisfaction against services provide by PDAM Tirta Kencana Samarinda City. As the sources of data are: the questionnaire by the amounts of respondents is 150 people (selected by using accidental sampling method), research point and the documents. The results of this research indicate that PDAM Tirta Kencana Samarinda City public service performance classified is relatively less good, by the value of Community Satisfaction Index of 2,48 and the conversion value is 62,21, this means the service quality is C. According to the performance analysis through Cartesian Diagram, shows that there are several dimensions urgently needed to be improve, i.e. service procedures, responsibility, service receive impartiality and service officer complaisance and hospitality.